Analisis Manfaat Penggunaan Aplikasi MY BEST di Universitas Bina Sarana Informatika (Metode System Usability Scale): (Metode System Usability Scale) - Putie Maharani Basa; Nurullah Sururi Afif; Sita Deliana; Salwa Gunawan; Anisa Yesi; Andhika Adriandra; Raihan Naufal (Elkom: Jurnal Elektronika dan Komputer, 2025)
The advancement of information technology has had a profound impact on education, including at the Universitas Bina Sarana Informatika (UBSI), where My Best, an elearning application, was created. With this program, users may participate in a variety of academic tasks, including online attendance, discussions, assessments, assignments, and course materials. But pupils continue to face usability difficulties. The System Usability Scale (SUS) technique is used in this study to assess the usability of the My Best program. The approach included 35 current UBSI students who have been using the My Best software for more than seven semesters. According to the assessment, the average SUS score was 70, which is considered to be rather high but still needs work in terms of interface usability and user-friendliness. As a result, although the My Best app is thought to be helpful in fostering learning, improvements are needed to enhance the whole user experience.